Pemberian Literasi Asuransi Kepada Guru di Jakarta - Alvernia Kurniartha; Wahyuari Wahyuari (IJEEM - Indonesian Journal of Environmental Education and Management, 2025)
The insurance industry plays a crucial role in the economy. It plays an active role and drives other financial industry groups, such as banking. The insurance industry and the banking industry are linked through investment, credit risk management, payment systems and transaction flows, as well as joint product collaborations obtain benefit to both parties. The Strategic Program in the Insurance Roadmap optimizes the connectivity between insurance and banking to provide benefits to customers and the societies. In fact, the societies is more comprehensively familiar with the banking industry than the insurance industry. People prefer to protect their finances by saving and investing through banks. Data from National Financial Literacy Survey (SNLKI-2024) conducted by Otoritas Jasa Keuangan (OJK) and Badan Pusat Statistics (BPS) shows a gap of 9.59% between the financial literacy index and the national financial inclusion index in 2023. This indicates that 9.59% of Indonesians who use financial products/services still lack of financial literacy adequate. Improving financial literacy and inclusion is crucial because adequate financial literacy impacts consumers' ability to understand the information they receive and assess the benefits and risks inherent in each financial product and service. STMA Trisakti Lecturer had completed Pengabdian kepada Masyarakat (PKM) activity during semester of 2024/2025 to provide insurance literacy to school teachers in Jakarta, considering school’s teachers is one of the targets of SNLKI Strategy (2021-2025) to get financial literacy. Insurance literacy through this PKM activity is expected to continue in further semester with the same or different target participants (in accordance with SNLKI targets). The purposes are to assist the Government in increasing national financial literacy rates/index, particularly insurance literacy. Hoped it will increase public awareness, regarding the importance of insurance and to support the national insurance growth. Keywords: National Financial Literacy and Inclusion Index, Insurance Literacy, Indonesian National Financial Literacy Strategy (SNLKI), STMA Trisakti, Community Service (PKM), Teachers.